Contribution of Superabsorbent Polymers to Growth and Yield of African Leafy Vegetables - Dorcas Ndunge Benard; J. P. O. Obiero; D. O. Mbuge (Advances in Agriculture, 2022)
Superabsorbent polymers (SAPs) have been used as water-saving materials for limited irrigation water resources in arid and semi-arid areas. The purpose of this study was to optimize SAP application dosage and irrigation intervals on the growth of African leafy vegetables (ALVs) under greenhouse conditions. A factorial experiment was conducted under greenhouse conditions to determine the optimal SAP application, dosage, and irrigation intervals for the growth and production of African leafy vegetables. Two species of African leafy vegetables were studied: cowpea (Vigna unguiculata) and African nightshade (Solanum scabrum). The experiment was performed in a randomized complete block design comprising 25 treatments: a factorial combination of five superabsorbent polymer application doses (0 g, 0.5 g, 1 g, 1.5 g, and 2 g) SAP/Kg of soil substrate and five irrigation intervals (3 days, 4 days, 5 days, 6 days, and 7 days) with three replications. Statistical analysis of the results showed that the use of SAP in irrigation can significantly promote the growth and yield of African leafy vegetables. SAP, irrigation, and their interactions significantly affected (P<0.005) the plant height, stem diameter, leaf area, number of mature leaves/plant, and dry weight of leafy vegetables. Treatment with SAP showed higher growth parameters and yield of vegetables compared to the treatments. Treatment with 1 g SAP/kg of soil substrate and 5-day irrigation interval recorded the highest plant growth and yield, with 24%, 11.7%, 11.1%, and 85.9% increase in cowpea plant height, leaf area, number of mature leaves, and dry weight/plant, respectively. The treatment with 1 g SAP/kg of soil substrate and 5-day irrigation interval was observed as the best for the optimal production of African leafy vegetables under greenhouse conditions. Hence, SAP could be a good strategy for food production within arid and semi-arid lands where water resources are scarce.